2018
DOI: 10.2147/ott.s169484
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis on the effect of angiogenesis blockade for the treatment of gastric cancer

Abstract: IntroductionTo date, anti-vascular endothelial growth factor (VEGF) monoclonal antibody (mAb, bevacizumab), anti-VEGF receptor mAb (ramucirumab) and selective vascular endothelial growth factor receptor (VEGFR) tyrosine kinase inhibitors (sunitinib, sorafenib and apatinib) have been tested in the clinical trials.Materials and methodsIn the current study, results of 32 clinical trials (24 Phase I or II, 8 Phase III) were systematically reviewed and meta-analysis was performed in 8 Phase III trial results.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Current evidence shows that angiogenesis is also involved in tumor metastasis. [61][62][63] A study by Yang et al suggested that depletion of Tiam1 could significantly suppress cervical cancer cell angiogenesis through inhibiting microtubule formation, blood vessels formation, as well as VEGF and VEGFA expression 20 Additionally, a recent study by Zhu et al also showed that Tiam1 overexpression could accelerate progression of lung adenocarcinoma by enhancing angiogenesis 32 Second, Tiam1 also has a role in regulating chemo-resistance of malignant cells. For instance, Hofbauer et al 24 reported that Tiam1/Rac1 signal transduction could contribute to chemoresistance of chronic lymphocytic leukemia cells.…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence shows that angiogenesis is also involved in tumor metastasis. [61][62][63] A study by Yang et al suggested that depletion of Tiam1 could significantly suppress cervical cancer cell angiogenesis through inhibiting microtubule formation, blood vessels formation, as well as VEGF and VEGFA expression 20 Additionally, a recent study by Zhu et al also showed that Tiam1 overexpression could accelerate progression of lung adenocarcinoma by enhancing angiogenesis 32 Second, Tiam1 also has a role in regulating chemo-resistance of malignant cells. For instance, Hofbauer et al 24 reported that Tiam1/Rac1 signal transduction could contribute to chemoresistance of chronic lymphocytic leukemia cells.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-angiogenic drugs employed in gastric cancer clinical trials mainly target VEGFA such as the monoclonal humanized antibody bevacizumab, or the VEGFR2, in particular ramucirumab and selective tyrosine kinase inhibitors such as sunitinib, sorafenib and apatinib. According to a very recent systematic review and meta-analysis the addition of anti-VEGFR2 targeting agents to the first- or second-line chemotherapy could prolong patient's OS and PFS in advanced or metastatic gastric cancer (16). The study also highlighted the inefficacy of anti-VEGFA therapy in this type of tumor, unlike what observed in other type of cancers (5356).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in gastric cancer patients high VEGFA levels have been associated with reduced survival and increased tumor aggressiveness (15). Anti-angiogenic therapy in gastric cancer patients did not so far meet the expectations despite some improvements have been observed (16). Thus, in order to improve the efficacy of anti-angiogenic therapy, it is of major importance to better characterize the vasculature associated with this tumor type.…”
Section: Introductionmentioning
confidence: 99%
“…Our results parallel data from F344 rats, in which an age-related decrease in bone blood flow was associated with lower ultimate bending stress of the central femur despite higher femoral BMD ( Bloomfield et al, 2002 ). An experiment that applies a second class of anti-angiogenic agents, such as tyrosine kinase inhibitors ( Lopez et al, 2019 ; Bai and Zhang, 2018 ), would be necessary to reveal whether low bone blood flow itself, rather than an intrinsic effect of this anti-VEGF antibody, causes low bone strength. In any case, our data indicate that bone blood flow is positively associated with whole bone strength with no effect on bone mass in red marrow trabecular bone rich regions (distal femoral metaphysis, LVB6, and proximal humeral metaphysis), suggesting that bone blood flow is a bone property that influences bone quality.…”
Section: Discussionmentioning
confidence: 99%